2012
DOI: 10.1074/jbc.m111.279364
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Conserved Hydrophobic Region of the Prion Protein and Dodecylphosphocholine Micelles

Abstract: The three-dimensional structure of PrP110 -136, a peptide encompassing the conserved hydrophobic region of the human prion protein, has been determined at high resolution in dodecylphosphocholine micelles by NMR. The results support the conclusion that the Ctm PrP, a transmembrane form of the prion protein, adopts a different conformation than the reported structures of the normal prion protein determined in solution. Paramagnetic relaxation enhancement studies with gadolinium-diethylenetriaminepentaacetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…The initial intent of this study was to characterize the conformation of huPrP(110–136) interacting at the surface of DPC micelles (red signals in Fig 1) observed in our previous report[11]. The spread of resonances for this surface species indicated that the conformation was structured.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…The initial intent of this study was to characterize the conformation of huPrP(110–136) interacting at the surface of DPC micelles (red signals in Fig 1) observed in our previous report[11]. The spread of resonances for this surface species indicated that the conformation was structured.…”
Section: Resultsmentioning
confidence: 86%
“…To illustrate the NMR data, a model of the surface-bound peptide was generated manually using Chimera[25] by using the Δδ 13 Cα data and the predicted backbone torsion angles (Φ,Ψ) (Fig 4). The peptide was also manually positioned on the micelle based on the PRE data from our previous study[11] using the α–helical micelle-inserted peptide model as a depth gauge.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations